High-strength road paving brick based on blast furnace slag and method for preparing the same
Patent Information
- Application Number
- CN202611399495.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-09
AI Technical Summary
常规处理方式难以充分协调骨料的孔隙特征与基体的粘结效能,导致最终制品往往在“渗透性能”与“宏观力学强度”之间难以兼顾,制约了该类固废基新材料的综合性能提升与规模化应用
本发明通过改性细矿渣骨料与改性粗矿渣骨料的协同改性处理,实现了高炉矿渣细骨料与高炉矿渣粗骨料在胶凝材料中的均匀分散与亲水性能的全面提升。高炉矿渣细骨料与高炉矿渣粗骨料亲水性能与分散性能的提升,使得混合料在搅拌与压制成型过程中,既能避免胶凝浆体过度聚集阻碍水分渗透通道,又能显著增强高炉矿渣细骨料、高炉矿渣粗骨料与胶凝材料之间的粘结牢固度,促使基层与面层在压制成型及养护过程中形成高度一体化的坚固整体。本发明制备的路面砖在保持优异抗压强度与耐磨性能的同时,整体具备优异的水分渗透能力,大幅提升了路面砖的吸水率与透水性能,满足高标准海绵城市建设与道路铺设应用需求的有益效果。
Smart Images

Figure CN122878089A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials and solid waste resource utilization technology, specifically to a high-strength paving brick based on blast furnace slag and its preparation method. Background Technology
[0002] In recent years, blast furnace slag, as a major metallurgical solid waste, has been widely used in the preparation of cement-based paving bricks due to its potential hydraulic properties and natural aggregate-like characteristics, demonstrating significant application value in solid waste resource utilization and sponge city construction.
[0003] However, existing technologies still face certain limitations when developing paving bricks with both high permeability and high strength using blast furnace slag aggregate. The physical morphology and surface characteristics of blast furnace slag aggregate itself make it difficult to maintain a stable and effective pore structure while preserving the overall mechanical strength of the material when combined with cementitious materials. Conventional processing methods struggle to adequately coordinate the porosity characteristics of the aggregate with the bonding performance of the matrix, often resulting in a trade-off between "permeability" and "macroscopic mechanical strength" in the final product. This restricts the comprehensive performance improvement and large-scale application of this type of solid waste-based new material.
[0004] Therefore, there is an urgent need to provide a paving brick that can effectively dispose of blast furnace slag and has both high strength and good permeability, so as to realize the large-scale and high-value utilization of metallurgical solid waste and meet the development needs of high-performance building materials. Summary of the Invention
[0005] The purpose of this invention is to provide a high-strength paving brick based on blast furnace slag and its preparation method, so as to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing high-strength paving bricks based on blast furnace slag includes the following steps: S1. Preparation and mixing: By mass, 800-850 parts of modified fine slag aggregate, 850-950 parts of modified coarse slag aggregate, 505-616 parts of cementitious material, 2-2.2 parts of water-reducing agent and 120-150 parts of water are mixed evenly to obtain a mixture. S2. Base layer forming: 60%-80% of the total mass of the mixture is loaded into the mold and pressed under a forming pressure of 3.0MPa-4.0MPa for 10s-20s to obtain the base layer blank; S3. Surface layer forming: 20%-40% of the total mass of the mixture is placed on the surface of the base blank, and pressed under a forming pressure of 3.0MPa-4.0MPa for 30s-50s to form the surface layer, thereby obtaining a formed blank composed of the surface layer and the base layer. S4. Curing: Curing the formed blanks to obtain high-strength paving bricks based on blast furnace slag.
[0007] Preferably, the method for preparing the modified fine slag aggregate includes the following steps: S11. By mass, wash 850-1000 parts of blast furnace slag fine aggregate until the pH of the supernatant is 7-9, discard the washing supernatant, add 1200-1500 parts of ethanol-water composite solvent and 10-15 parts of γ-aminopropyltriethoxysilane, stir and react at 40℃-50℃ for 1-2 hours, filter and wash with water, and dry at 105℃ to constant weight to obtain cationic slag fine aggregate; S12. Add 30-50 parts of modified attapulgite additive and 2-6 parts of dispersant to 1000-1300 parts of water and ultrasonically disperse evenly to obtain a pre-dispersion liquid; add 800-950 parts of cationic slag fine aggregate and 8-15 parts of complexing agent to 1000-1300 parts of water and stir for 10-30 minutes to obtain a pre-complexed slag dispersion liquid; S13. Add the pre-complexed slag dispersion to the pre-dispersion liquid and mix evenly. Add 80-120 parts of monomer mixture and 1-5 parts of crosslinking agent, stir for 10-30 minutes, adjust the pH of the system to 7-9, introduce inert gas to remove oxygen, add 0.3-1.5 parts of initiator, and react at 60℃-80℃ for 2-4 hours to obtain wet blast furnace slag fine aggregate. S14. Drain the wet blast furnace slag fine aggregate, then immerse it in a crosslinking curing agent with a mass fraction of 5%-15%, react at 40℃-60℃ for 1-3 hours, wash and dry at 60℃-80℃ to obtain modified fine blast furnace slag aggregate.
[0008] Preferably, the method for preparing the modified coarse slag aggregate includes the following steps: S21. By mass, 900-1000 parts of blast furnace slag coarse aggregate are immersed in 1000 parts of a dispersion of nano-calcium carbonate containing sodium polyacrylate composite, and soaked at 20℃-40℃ for 2h-6h to obtain primary sealing aggregate. S22. Immerse the initial sealing aggregate in 1000 parts of a dispersion containing nano-kaolin and polycarboxylate superplasticizer, soak at 20℃-40℃ for 1h-3h, and then dry to obtain modified coarse slag aggregate.
[0009] Preferably, the preparation method of the modified attapulgite additive includes the following steps: S111. Add the attapulgite nanorods to a 3 mol / L-6 mol / L hydrochloric acid solution and perform acid leaching treatment for 2 h-4 h. After washing until neutral and drying, acid-activated attapulgite nanorods are obtained. S112. Acid-activated attapulgite nanorods are dispersed in an alcohol-water mixed solvent, and methacryloxypropyltrimethoxysilane is added. The mixture is then heated and refluxed at 60℃-80℃ for 2-4 hours. After the treatment, the mixture is centrifuged, washed, and dried to obtain the modified attapulgite additive.
[0010] Preferably, the cementing material includes ordinary silicate cement, fly ash, and silica fume; The mass ratio of the ordinary silicate cement, fly ash, and silica fume is (90-110):10:(0.9-3.3); The water-reducing agent is a polycarboxylate water-reducing agent.
[0011] Preferably, the mass ratio of ethanol to water in the ethanol-water composite solvent is (2-5):1; The dispersant is sodium hexametaphosphate; The complexing agent is one or more of disodium ethylenediaminetetraacetate, sodium citrate, or sodium gluconate. The monomer mixture is composed of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid in a mass ratio of (1-3):1; The crosslinking agent is N,N'-methylenebisacrylamide; The initiator is one or a combination of two of ammonium persulfate or potassium persulfate; The cross-linking curing agent is either calcium chloride solution or calcium nitrate solution.
[0012] Preferably, in the dispersion of nano-calcium carbonate containing sodium polyacrylate composite, the mass ratio of nano-calcium carbonate, sodium polyacrylate and water is (5-10):(1-3):(87-94). In the dispersion containing nano-metakaolin and polycarboxylate superplasticizer, the mass ratio of nano-metakaolin, polycarboxylate superplasticizer and water is (5-15):(2-10):(75-93).
[0013] Preferably, the mass ratio of the attapulgite nanorods to the hydrochloric acid solution is 1:(5-15); The mass ratio of water to ethanol in the alcohol-water mixed solvent is 1:5-1:10; The mass ratio of the acid-activated attapulgite nanorods to the alcohol-water mixed solvent is 1:(10-30); The amount of methacryloyloxypropyltrimethoxysilane added is 5%-20% of the mass of the acid-activated attapulgite nanorods.
[0014] Preferably, in step S4, the curing conditions are as follows: after curing in the mold for 24-48 hours under standard curing conditions of temperature 20±2℃ and relative humidity ≥95%, the mold is removed, and curing continues under standard curing conditions for 28 days.
[0015] A high-strength paving brick based on blast furnace slag was prepared by the above-mentioned method.
[0016] Compared with the prior art, the beneficial effects of the present invention are: This invention achieves a comprehensive improvement in the uniform dispersion and hydrophilicity of blast furnace slag fine and coarse aggregates in cementitious materials through synergistic modification of these aggregates. The enhanced hydrophilicity and dispersion properties of the blast furnace slag fine and coarse aggregates prevent excessive aggregation of the cementitious slurry from hindering water penetration during mixing and pressing. It also significantly strengthens the bond between the blast furnace slag fine and coarse aggregates and the cementitious materials, promoting a highly integrated and robust whole between the base layer and surface layer during pressing and curing. The paving bricks prepared by this invention maintain excellent compressive strength and wear resistance while possessing excellent overall water permeability, significantly improving the water absorption and permeability of the paving bricks, thus meeting the beneficial requirements of high-standard sponge city construction and road paving applications. Attached Figure Description
[0017] Figure 1 This is a process flow diagram of the preparation process of high-strength paving bricks based on blast furnace slag according to the present invention; Figure 2 This is a process flow diagram for preparing the modified fine slag aggregate of the present invention; Figure 3 This is a process flow diagram for preparing the modified coarse slag aggregate of the present invention; Figure 4 This is a process flow diagram for preparing the modified attapulgite clay additive of the present invention; Figure 5 This is a physical image of the high-strength paving brick based on blast furnace slag obtained in Embodiment 3 of the present invention. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Please see Figures 1-5 The present invention provides a technical solution: Example 1 1. Preparation of modified attapulgite clay additives: S111. Add 60g of attapulgite nanorods to 300g of 3mol / L hydrochloric acid solution and perform acid leaching treatment for 2h. After washing until neutral and drying, acid-activated attapulgite nanorods are obtained. S112. Add 50g of acid-activated attapulgite nanorods to 500g of alcohol-water mixed solvent (the alcohol-water mixed solvent is prepared by mixing 150g of water and 750g of anhydrous ethanol, and 500g of it is used), then add 2.5g of methacryloyloxypropyltrimethoxysilane, heat and reflux at 60℃ for 2h, and after treatment, centrifuge, wash and dry to obtain modified attapulgite additive.
[0020] 2. Preparation of modified fine slag aggregate: S11. Wash 850g of blast furnace slag fine aggregate (particle size 2.36mm-4.75mm) until the pH of the supernatant is 7. Discard the washing supernatant, then add 1200g of ethanol-water composite solvent (ethanol-water composite solvent is prepared by mixing 400g of water and 800g of anhydrous ethanol) and 10g of γ-aminopropyltriethoxysilane. Stir the reaction at 40℃ for 1h, filter and wash with water, and dry at 105℃ to constant weight to obtain cationic slag fine aggregate. S12. Add 30g of modified attapulgite additive and 2g of sodium hexametaphosphate to 1000g of water and ultrasonically disperse evenly to obtain a pre-dispersion liquid; add 800g of cationic slag fine aggregate and 8g of disodium ethylenediaminetetraacetate to 1000g of water and stir for 10min to obtain a pre-complexed slag dispersion liquid. S13. Add the pre-complexed slag dispersion to the pre-dispersion liquid and mix evenly. Add 80g of monomer mixture (the monomer mixture is composed of 40g acrylamide and 40g 2-acrylamide-2-methylpropanesulfonic acid) and 1g N,N'-methylenebisacrylamide. Stir for 10min, adjust the pH of the system to 7, purge with nitrogen to remove oxygen, and then add 0.3g of ammonium persulfate. React at 60℃ for 2h to obtain wet blast furnace slag fine aggregate. S14. Drain the wet blast furnace slag fine aggregate, immerse it in 2000g of 5% calcium chloride solution, react at 40℃ for 1h, wash and dry at 60℃ to obtain modified fine blast furnace slag aggregate. 3. Preparation of modified coarse slag aggregate: S21. Immerse 900g of blast furnace slag coarse aggregate (particle size 4.75mm-9mm) in a dispersion prepared by mixing 50g of nano calcium carbonate, 10g of sodium polyacrylate and 940g of water, and soak at 20℃ for 2h to obtain primary sealing aggregate. S22. The initial sealing aggregate is immersed in a dispersion prepared by mixing 50g of nano-kaolin, 20g of polycarboxylate superplasticizer and 930g of water, soaked at 20℃ for 1 hour, and then dried to obtain modified coarse slag aggregate.
[0021] 4. Preparation and mixing: Weigh out 800g of modified fine slag aggregate, 850g of modified coarse slag aggregate, 505g of cementitious material (including 450g of ordinary silicate cement, 50g of fly ash, and 5g of silica fume), 2g of polycarboxylate superplasticizer, and 120g of water, and mix them evenly to obtain the mixture.
[0022] 5. Layered pressing molding and curing: 60% of the total mass of the mixture (i.e., 1366.2g) was loaded into a mold and pressed for 10 seconds at a molding pressure of 3.0MPa to obtain the base layer green body. Subsequently, 40% of the total mass of the mixture (i.e., 910.8g) was placed on the surface of the base layer green body and pressed for 30 seconds at a molding pressure of 3.0MPa to form the surface layer, thus obtaining the molded green body. The molded green body was cured in the mold for 24 hours under standard curing conditions of 20℃ and 95% relative humidity, and then demolded. It was then cured under standard curing conditions for another 28 days to obtain a high-strength paving brick based on blast furnace slag.
[0023] Example 2 1. Preparation of modified attapulgite clay additives: S111. Add 60g of attapulgite nanorods to 900g of 6mol / L hydrochloric acid solution and perform acid leaching treatment for 4h. After washing until neutral and drying, acid-activated attapulgite nanorods are obtained. S112. Add 50g of acid-activated attapulgite nanorods to 1500g of alcohol-water mixed solvent (the alcohol-water mixed solvent is prepared by mixing 150g of water and 1500g of anhydrous ethanol, and 1500g of it is used), then add 10g of methacryloyloxypropyltrimethoxysilane, and heat and reflux at 80℃ for 4h. After the treatment, centrifuge, wash and dry to obtain modified attapulgite additive.
[0024] 2. Preparation of modified fine slag aggregate: S11. Wash 1000g of blast furnace slag fine aggregate (particle size 2.36mm-4.75mm) until the pH of the supernatant is 9. Discard the washing supernatant, then add 1500g of ethanol-water composite solvent (ethanol-water composite solvent is prepared by mixing 250g of water and 1250g of anhydrous ethanol) and 15g of γ-aminopropyltriethoxysilane. Stir the reaction at 50℃ for 2h, filter and wash with water, and dry at 105℃ to constant weight to obtain cationic slag fine aggregate. S12. Add 50g of modified attapulgite additive and 6g of sodium hexametaphosphate to 1300g of water and ultrasonically disperse evenly to obtain a pre-dispersion liquid; add 950g of cationic slag fine aggregate and 15g of disodium ethylenediaminetetraacetate to 1300g of water and stir for 30min to obtain a pre-complexed slag dispersion liquid. S13. Add the pre-complexed slag dispersion to the pre-dispersion liquid and mix evenly. Add 120g of monomer mixture (the monomer mixture is composed of 90g of acrylamide and 30g of 2-acrylamide-2-methylpropanesulfonic acid) and 5g of N,N'-methylenebisacrylamide. Stir for 30min, adjust the pH of the system to 9, purge with nitrogen to remove oxygen, and then add 1.5g of ammonium persulfate. React at 80℃ for 4h to obtain wet fine aggregate of blast furnace slag. S14. Drain the wet blast furnace slag fine aggregate, immerse it in 2500g of 15% calcium chloride solution, react at 60℃ for 3h, wash and dry at 80℃ to obtain modified fine blast furnace slag aggregate.
[0025] 3. Preparation of modified coarse slag aggregate: S21. Immerse 1000g of blast furnace slag coarse aggregate (particle size 4.75mm-9mm) in a dispersion prepared by mixing 100g of nano calcium carbonate, 30g of sodium polyacrylate and 870g of water, and soak at 40℃ for 6h to obtain primary sealing aggregate. S22. The initial sealing aggregate is immersed in a dispersion prepared by mixing 150g of nano-kaolin, 100g of polycarboxylate superplasticizer and 750g of water, soaked at 40℃ for 3h, and then dried to obtain modified coarse slag aggregate.
[0026] 4. Preparation and mixing: Weigh out 850g of modified fine slag aggregate, 950g of modified coarse slag aggregate, 616g of cementitious materials (including 550g of ordinary silicate cement, 50g of fly ash, and 16g of silica fume), 2.2g of polycarboxylate superplasticizer, and 150g of water, and mix them evenly to obtain the mixture.
[0027] 5. Layered pressing molding and curing: 80% of the total mass of the mixture (2054.6g) was loaded into a mold and pressed for 20 seconds at a molding pressure of 4.0MPa to obtain the base layer. Then, 20% of the total mass of the mixture (513.6g) was placed on the surface of the base layer and pressed for 50 seconds at a molding pressure of 4.0MPa to form the surface layer, resulting in the molded green body. The molded green body was cured in the mold for 48 hours under standard curing conditions of 20℃ and 95% relative humidity, then demolded and cured for another 28 days under standard curing conditions to obtain a high-strength paving brick based on blast furnace slag.
[0028] Example 3 1. Preparation of modified attapulgite clay additives: S111. Add 60g of attapulgite nanorods to 600g of 5mol / L hydrochloric acid solution and perform acid leaching treatment for 3h. After washing until neutral and drying, acid-activated attapulgite nanorods are obtained. S112. Add 50g of acid-activated attapulgite nanorods to 1000g of alcohol-water mixed solvent (the alcohol-water mixed solvent is prepared by mixing 150g of water and 1200g of anhydrous ethanol, and 1000g of it is used), then add 7.5g of methacryloyloxypropyltrimethoxysilane, heat and reflux at 70℃ for 3h, and after treatment, centrifuge, wash and dry to obtain modified attapulgite additive.
[0029] 2. Preparation of modified fine slag aggregate: S11. Wash 900g of blast furnace slag fine aggregate (particle size 2.36mm-4.75mm) until the pH of the supernatant is 8. Discard the washing supernatant, then add 1300g of ethanol-water composite solvent (ethanol-water composite solvent is prepared by mixing 330g of water and 990g of anhydrous ethanol) and 12g of γ-aminopropyltriethoxysilane. Stir and react at 45℃ for 1.5h, filter and wash with water, and dry at 105℃ to constant weight to obtain cationic slag fine aggregate. S12. Add 40g of modified attapulgite additive and 3g of sodium hexametaphosphate to 1200g of water and ultrasonically disperse evenly to obtain a pre-dispersion liquid; add 900g of cationic slag fine aggregate and 12g of disodium ethylenediaminetetraacetate to 1200g of water and stir for 20min to obtain a pre-complexed slag dispersion liquid. S13. Add the pre-complexed slag dispersion to the pre-dispersion liquid and mix evenly. Add 100g of monomer mixture (the monomer mixture is composed of 50g acrylamide and 50g 2-acrylamide-2-methylpropanesulfonic acid) and 3g N,N'-methylenebisacrylamide. Stir for 20min, adjust the pH of the system to 8, purge with nitrogen to remove oxygen, and then add 0.8g of ammonium persulfate. React at 70℃ for 3h to obtain wet blast furnace slag fine aggregate. S14. Drain the wet blast furnace slag fine aggregate, immerse it in 2200g of 10% calcium chloride solution, react at 50℃ for 2h, wash and dry at 70℃ to obtain modified fine blast furnace slag aggregate.
[0030] 3. Preparation of modified coarse slag aggregate: S21. Immerse 900g of blast furnace slag coarse aggregate (particle size 4.75mm-9mm) in a dispersion prepared by mixing 70g of nano calcium carbonate, 20g of sodium polyacrylate and 910g of water, and soak at 30℃ for 4h to obtain primary sealing aggregate. S22. The initial sealing aggregate is immersed in a dispersion prepared by mixing 100g of nano-kaolin, 60g of polycarboxylate superplasticizer and 840g of water, soaked at 30℃ for 2h, and then dried to obtain modified coarse slag aggregate.
[0031] 4. Preparation and mixing: Weigh out 850g of modified fine slag aggregate, 900g of modified coarse slag aggregate, 561g of cementitious material (including 500g of ordinary silicate cement, 50g of fly ash, and 11g of silica fume), 2.2g of polycarboxylate superplasticizer, and 140g of water, and mix them evenly to obtain the mixture.
[0032] 5. Layered pressing molding and curing: 60% of the total mass of the mixture (i.e., 1471.9g) was loaded into a mold and pressed under a molding pressure of 3.5MPa for 15s to obtain the base layer green body. Subsequently, 40% of the total mass of the mixture (i.e., 981.3g) was placed on the surface of the base layer green body and pressed under a molding pressure of 3.5MPa for 40s to form the surface layer, thus obtaining the molded green body. The molded green body was cured in the mold for 36 hours under standard curing conditions of 20℃ and 95% relative humidity, and then demolded. It was then cured under standard curing conditions for another 28 days to obtain a high-strength paving brick based on blast furnace slag.
[0033] The high-strength paving bricks based on blast furnace slag prepared in Example 3, such as Figure 5 As shown, the paving bricks are regular rectangular blocks with a rough, aggregated surface formed by modified blast furnace slag aggregate and cementitious materials, resulting in a solid texture. Morphologically, the bricks exhibit a complete structure without visible cracks, chipped corners, or delamination. Permeable pores are visible on the surface, clearly demonstrating the excellent integrity and molding quality achieved through the synergistic modification of coarse and fine aggregates and the layered pressing process, meeting the appearance requirements for high-strength permeable paving bricks.
[0034] Comparative Example 1 The difference from Example 3 is that no modification treatment is performed on the fine slag aggregate.
[0035] The specific steps are as follows: cancel the "preparation of modified fine slag aggregate" step in Example 3, directly weigh 850g of unmodified blast furnace slag fine aggregate (particle size 2.36mm-4.75mm), mix it with the same mass of modified coarse slag aggregate, cementitious material, water-reducing agent and water in Example 3, and the subsequent layered pressing molding and curing steps are the same as in Example 3.
[0036] Comparative Example 2 The difference from Example 3 is that no sealing modification treatment is applied to the coarse slag aggregate.
[0037] The specific steps are as follows: cancel the "preparation of modified coarse slag aggregate" step in Example 3, directly weigh 900g of unmodified blast furnace slag coarse aggregate (particle size 4.75mm-9mm), mix it with the same mass of modified fine slag aggregate, cementitious material, water-reducing agent and water in Example 3, and the subsequent layered pressing molding and curing steps are the same as in Example 3.
[0038] Comparative Example 3 The difference from Example 3 is that no modification treatment is performed on the fine slag aggregate and the coarse slag aggregate.
[0039] The specific steps are as follows: the steps of "preparation of modified fine slag aggregate" and "preparation of modified coarse slag aggregate" in Example 3 are cancelled. 850g of unmodified blast furnace slag fine aggregate (particle size 2.36mm-4.75mm) and 900g of unmodified blast furnace slag coarse aggregate (particle size 4.75mm-9mm) are weighed directly and mixed with the same mass of cementitious material, water-reducing agent and water as in Example 3. The subsequent layered pressing molding and curing steps are the same as in Example 3.
[0040] Comparative Example 4 The difference from Example 3 is that it is formed by one-time pressing and does not involve layer pressing.
[0041] The specific steps are as follows: Prepare and mix materials according to the proportions in Example 3 to obtain a mixture (i.e., using modified fine slag aggregate and modified coarse slag aggregate). Put all the mixture (100%) into the mold at one time, press it under a molding pressure of 3.5MPa for 40s to obtain a molded blank. The subsequent curing steps are the same as in Example 3.
[0042] Performance Testing and Results Analysis According to the relevant standards of "Concrete Pavement Bricks" (GB / T 28635-2012) and "Permeable Pavement Bricks and Permeable Pavement Panels" (GB / T25993-2023), the pavement bricks prepared in Examples 1-3 and Comparative Examples 1-4 were tested for 28-day compressive strength, splitting tensile strength, permeability coefficient, pitting length (wear resistance), and strength loss rate after freeze-thaw cycles. The test results are shown in Table 1.
[0043] Table 1: Performance test results of paving bricks in the examples and comparative examples As shown in Table 1, Examples 1-3 are superior to Comparative Examples 1-4 in terms of 28-day compressive strength, splitting tensile strength, permeability coefficient, pit length, and strength loss rate after freeze-thaw cycles. Among them, Example 3 has the best overall performance.
[0044] In Comparative Example 3, neither the coarse nor fine aggregates were modified, and the compressive strength (24.5 MPa) and permeability coefficient (1.15 × 10⁻⁶) were similar. -2 The permeability coefficient was lowest in both cm / s, but the length of the grinding pit and the rate of strength loss after freeze-thaw were the highest; in Comparative Example 1, only the coarse aggregate was modified, and the permeability coefficient was reduced to 1.35×10. -2 cm / s; Comparative Example 2 only modified fine aggregate, the permeability coefficient is acceptable (1.80×10 cm / s); -2However, the coarse aggregate was not sealed for reinforcement, and the compressive strength dropped to 26.8 MPa. Comparing Example 3 with Comparative Example 4, it can be seen that one-time pressing molding resulted in insufficient surface density, increased the grinding pit length to 22.8 mm, decreased wear resistance, and the compressive strength and freeze-thaw resistance were also inferior to Example 3.
[0045] In summary, this invention overcomes the technical bottleneck of traditional slag paving bricks, which struggle to balance high permeability and high mechanical strength, through synergistic modification of coarse and fine aggregates and a layered pressing process. The resulting paving bricks achieve a 28-day compressive strength of 39.1 MPa and a permeability coefficient of 2.25 × 10⁻⁶. -2 It has a speed of cm / s and also has good wear resistance and freeze-thaw resistance, making it suitable for sponge city construction.
[0046] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing high-strength paving bricks based on blast furnace slag, characterized in that, Includes the following steps: S1. Preparation and mixing: By mass, 800-850 parts of modified fine slag aggregate, 850-950 parts of modified coarse slag aggregate, 505-616 parts of cementitious material, 2-2.2 parts of water-reducing agent and 120-150 parts of water are mixed evenly to obtain a mixture. S2. Base layer forming: 60%-80% of the total mass of the mixture is loaded into the mold and pressed under a forming pressure of 3.0MPa-4.0MPa for 10s-20s to obtain the base layer blank; S3. Surface layer forming: 20%-40% of the total mass of the mixture is placed on the surface of the base blank, and pressed under a forming pressure of 3.0MPa-4.0MPa for 30s-50s to form the surface layer, thereby obtaining a formed blank composed of the surface layer and the base layer. S4. Curing: Curing the formed blanks to obtain high-strength paving bricks based on blast furnace slag.
2. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 1, characterized in that, The method for preparing the modified fine slag aggregate includes the following steps: S11. By mass, wash 850-1000 parts of blast furnace slag fine aggregate until the pH of the supernatant is 7-9, discard the washing supernatant, add 1200-1500 parts of ethanol-water composite solvent and 10-15 parts of γ-aminopropyltriethoxysilane, stir and react at 40℃-50℃ for 1-2 hours, filter and wash with water, and dry at 105℃ to constant weight to obtain cationic slag fine aggregate; S12. Add 30-50 parts of modified attapulgite additive and 2-6 parts of dispersant to 1000-1300 parts of water and ultrasonically disperse evenly to obtain a pre-dispersion liquid; add 800-950 parts of cationic slag fine aggregate and 8-15 parts of complexing agent to 1000-1300 parts of water and stir for 10-30 minutes to obtain a pre-complexed slag dispersion liquid; S13. Add the pre-complexed slag dispersion to the pre-dispersion liquid and mix evenly. Add 80-120 parts of monomer mixture and 1-5 parts of crosslinking agent, stir for 10-30 minutes, adjust the pH of the system to 7-9, introduce inert gas to remove oxygen, add 0.3-1.5 parts of initiator, and react at 60℃-80℃ for 2-4 hours to obtain wet blast furnace slag fine aggregate. S14. Drain the wet blast furnace slag fine aggregate, then immerse it in a crosslinking curing agent with a mass fraction of 5%-15%, react at 40℃-60℃ for 1-3 hours, wash and dry at 60℃-80℃ to obtain modified fine blast furnace slag aggregate.
3. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 1, characterized in that, The method for preparing the modified coarse slag aggregate includes the following steps: S21. By mass, 900-1000 parts of blast furnace slag coarse aggregate are immersed in 1000 parts of a dispersion of nano-calcium carbonate containing sodium polyacrylate composite, and soaked at 20℃-40℃ for 2h-6h to obtain primary sealing aggregate. S22. Immerse the initial sealing aggregate in 1000 parts of a dispersion containing nano-kaolin and polycarboxylate superplasticizer, soak at 20℃-40℃ for 1h-3h, and then dry to obtain modified coarse slag aggregate.
4. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 2, characterized in that, The preparation method of the modified attapulgite additive includes the following steps: S111. Add the attapulgite nanorods to a 3 mol / L-6 mol / L hydrochloric acid solution and perform acid leaching treatment for 2 h-4 h. After washing until neutral and drying, acid-activated attapulgite nanorods are obtained. S112. Acid-activated attapulgite nanorods are dispersed in an alcohol-water mixed solvent, and methacryloxypropyltrimethoxysilane is added. The mixture is then heated and refluxed at 60℃-80℃ for 2-4 hours. After the treatment, the mixture is centrifuged, washed, and dried to obtain the modified attapulgite additive.
5. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 1, characterized in that, The cementing materials include ordinary silicate cement, fly ash, and silica fume; The mass ratio of the ordinary silicate cement, fly ash, and silica fume is (90-110):10:(0.9-3.3); The water-reducing agent is a polycarboxylate water-reducing agent.
6. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 2, characterized in that, The mass ratio of ethanol to water in the ethanol-water composite solvent is (2-5):1; The dispersant is sodium hexametaphosphate; The complexing agent is one or more of disodium ethylenediaminetetraacetate, sodium citrate, or sodium gluconate. The monomer mixture is composed of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid in a mass ratio of (1-3):1; The crosslinking agent is N,N'-methylenebisacrylamide; The initiator is one or a combination of two of ammonium persulfate or potassium persulfate; The cross-linking curing agent is either calcium chloride solution or calcium nitrate solution.
7. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 3, characterized in that, In the dispersion of nano-calcium carbonate containing sodium polyacrylate, the mass ratio of nano-calcium carbonate, sodium polyacrylate and water is (5-10):(1-3):(87-94). In the dispersion containing nano-metakaolin and polycarboxylate superplasticizer, the mass ratio of nano-metakaolin, polycarboxylate superplasticizer and water is (5-15):(2-10):(75-93).
8. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 4, characterized in that, The mass ratio of the attapulgite nanorods to the hydrochloric acid solution is 1:(5-15); The mass ratio of water to ethanol in the alcohol-water mixed solvent is 1:5-1:10; The mass ratio of the acid-activated attapulgite nanorods to the alcohol-water mixed solvent is 1:(10-30); The amount of methacryloyloxypropyltrimethoxysilane added is 5%-20% of the mass of the acid-activated attapulgite nanorods.
9. The method for preparing high-strength paving bricks based on blast furnace slag according to claim 1, characterized in that, In step S4, the curing conditions are as follows: under standard curing conditions of 20±2℃ and relative humidity ≥95%, the mold is cured for 24h-48h, then demolded, and cured under standard curing conditions for 28 days.
10. A high-strength paving brick based on blast furnace slag, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.